PENENTUAN JURUSAN KE PERGURUAN TINGGI MENGGUNAKAN METODE CLUSTERING DI SMAN 3 KUALA TUNGKAL - ., SABARIAH; ISTONINGTYAS, MARRYLINTERI; ., SHARIPUDDIN (LPPM Universitas Dinamika Bangsa, 2018)
SMA Negeri 3 Kuala Tungkal is one of the high schools located in the city of Kuala Tungkal which is located at Jalan Beringin Kelurahan Petunas Tungkal Ilir Sub-district, Tanjung Jabung Barat Regency, Jambi Province, which has 293 students divided into 2 majors, IPA and IPS. The problems students find are determining which courses they take on the basis of parental choices, following friends, or simply choosing without knowing whether the courses chosen match their interests and talents. As a result after entering college students are experiencing difficulties and feel the wrong direction so that the authors provide solutions for the determination of the majors to the college using the method of k-means clustering with k-means clustering method is that students can know what department is suitable for them to enter after they graduate school and want to continue their education to college. So they no longer feel the wrong majors and difficult in receiving the lessons given to them because they already know the majors they want according to their own interests and interests Keywords: Majoring, Clustering, K-Means